Comparison of methods for recruiting and engaging parents in online interventions: study protocol for the Cry Baby infant sleep and settling program. Issue 1 (December 2015) - Cook, Fallon; Seymour, Monique; Giallo, Rebecca; Cann, Warren; Nicholson, Jan; Green, Julie; Hiscock, Harriet
Abstract Background Anticipatory guidance around the management of sleep and crying problems in early infancy has been shown to improve both infant behaviour and parent symptoms of postnatal depression. Digital technology offers platforms for making such programs widely available in a cost-efficient manner. However, it remains unclear who accesses online parenting advice and in particular, whether the parents who would most benefit are represented amongst users. It is also unknown whether the uptake of online programs can be improved by health professional recommendations, or whether parents require additional prompts and reminders to use the program. In this study we aim to: (1) determine whether weekly email prompts increase engagement with and use of a brief online program about infant sleeping and crying, (2) determine whether encouragement from a maternal and child health nurse promotes greater engagement with and use of the program, (3) examine who uses a brief online program about infant sleeping and crying; and, (4) examine the psychosocial characteristics of participants. Methods/Design This study is a randomised, parallel group, superiority trial, with all participating primary carers of infants aged 2 to 12 weeks, receiving access to the online program. Two modes of recruitment will be compared: recruitment via an online notice published on a non-commercial, highly credible and evidence-based website for parents and carers and via the parent's Maternal and Child Health nurse. After baseline assessment, parents will be randomised to one of two support conditions: online program alone or online program plus weekly email prompts. Follow up data will be collected at 4 months of infant age. Discussion Results from this trial will indicate whether involvement from a health professional, and/or ongoing email contact is necessary to engage parents in a brief online intervention, and promote parental use of strategies suggested within the program. Results of this trial will inform the development of recruitment and engagement strategies for other online interventions. Trial registration Australian New Zealand Clinical Trials Registry:ACTRN12613001098729 . Registered 01 October 2013.